If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 5)(x + -2) + 3(x + 10)(x + -18) = 18(x + 50) + -1(x + -36) Reorder the terms: 6(5 + x)(x + -2) + 3(x + 10)(x + -18) = 18(x + 50) + -1(x + -36) Reorder the terms: 6(5 + x)(-2 + x) + 3(x + 10)(x + -18) = 18(x + 50) + -1(x + -36) Multiply (5 + x) * (-2 + x) 6(5(-2 + x) + x(-2 + x)) + 3(x + 10)(x + -18) = 18(x + 50) + -1(x + -36) 6((-2 * 5 + x * 5) + x(-2 + x)) + 3(x + 10)(x + -18) = 18(x + 50) + -1(x + -36) 6((-10 + 5x) + x(-2 + x)) + 3(x + 10)(x + -18) = 18(x + 50) + -1(x + -36) 6(-10 + 5x + (-2 * x + x * x)) + 3(x + 10)(x + -18) = 18(x + 50) + -1(x + -36) 6(-10 + 5x + (-2x + x2)) + 3(x + 10)(x + -18) = 18(x + 50) + -1(x + -36) Combine like terms: 5x + -2x = 3x 6(-10 + 3x + x2) + 3(x + 10)(x + -18) = 18(x + 50) + -1(x + -36) (-10 * 6 + 3x * 6 + x2 * 6) + 3(x + 10)(x + -18) = 18(x + 50) + -1(x + -36) (-60 + 18x + 6x2) + 3(x + 10)(x + -18) = 18(x + 50) + -1(x + -36) Reorder the terms: -60 + 18x + 6x2 + 3(10 + x)(x + -18) = 18(x + 50) + -1(x + -36) Reorder the terms: -60 + 18x + 6x2 + 3(10 + x)(-18 + x) = 18(x + 50) + -1(x + -36) Multiply (10 + x) * (-18 + x) -60 + 18x + 6x2 + 3(10(-18 + x) + x(-18 + x)) = 18(x + 50) + -1(x + -36) -60 + 18x + 6x2 + 3((-18 * 10 + x * 10) + x(-18 + x)) = 18(x + 50) + -1(x + -36) -60 + 18x + 6x2 + 3((-180 + 10x) + x(-18 + x)) = 18(x + 50) + -1(x + -36) -60 + 18x + 6x2 + 3(-180 + 10x + (-18 * x + x * x)) = 18(x + 50) + -1(x + -36) -60 + 18x + 6x2 + 3(-180 + 10x + (-18x + x2)) = 18(x + 50) + -1(x + -36) Combine like terms: 10x + -18x = -8x -60 + 18x + 6x2 + 3(-180 + -8x + x2) = 18(x + 50) + -1(x + -36) -60 + 18x + 6x2 + (-180 * 3 + -8x * 3 + x2 * 3) = 18(x + 50) + -1(x + -36) -60 + 18x + 6x2 + (-540 + -24x + 3x2) = 18(x + 50) + -1(x + -36) Reorder the terms: -60 + -540 + 18x + -24x + 6x2 + 3x2 = 18(x + 50) + -1(x + -36) Combine like terms: -60 + -540 = -600 -600 + 18x + -24x + 6x2 + 3x2 = 18(x + 50) + -1(x + -36) Combine like terms: 18x + -24x = -6x -600 + -6x + 6x2 + 3x2 = 18(x + 50) + -1(x + -36) Combine like terms: 6x2 + 3x2 = 9x2 -600 + -6x + 9x2 = 18(x + 50) + -1(x + -36) Reorder the terms: -600 + -6x + 9x2 = 18(50 + x) + -1(x + -36) -600 + -6x + 9x2 = (50 * 18 + x * 18) + -1(x + -36) -600 + -6x + 9x2 = (900 + 18x) + -1(x + -36) Reorder the terms: -600 + -6x + 9x2 = 900 + 18x + -1(-36 + x) -600 + -6x + 9x2 = 900 + 18x + (-36 * -1 + x * -1) -600 + -6x + 9x2 = 900 + 18x + (36 + -1x) Reorder the terms: -600 + -6x + 9x2 = 900 + 36 + 18x + -1x Combine like terms: 900 + 36 = 936 -600 + -6x + 9x2 = 936 + 18x + -1x Combine like terms: 18x + -1x = 17x -600 + -6x + 9x2 = 936 + 17x Solving -600 + -6x + 9x2 = 936 + 17x Solving for variable 'x'. Reorder the terms: -600 + -936 + -6x + -17x + 9x2 = 936 + 17x + -936 + -17x Combine like terms: -600 + -936 = -1536 -1536 + -6x + -17x + 9x2 = 936 + 17x + -936 + -17x Combine like terms: -6x + -17x = -23x -1536 + -23x + 9x2 = 936 + 17x + -936 + -17x Reorder the terms: -1536 + -23x + 9x2 = 936 + -936 + 17x + -17x Combine like terms: 936 + -936 = 0 -1536 + -23x + 9x2 = 0 + 17x + -17x -1536 + -23x + 9x2 = 17x + -17x Combine like terms: 17x + -17x = 0 -1536 + -23x + 9x2 = 0 Begin completing the square. Divide all terms by 9 the coefficient of the squared term: Divide each side by '9'. -170.6666667 + -2.555555556x + x2 = 0 Move the constant term to the right: Add '170.6666667' to each side of the equation. -170.6666667 + -2.555555556x + 170.6666667 + x2 = 0 + 170.6666667 Reorder the terms: -170.6666667 + 170.6666667 + -2.555555556x + x2 = 0 + 170.6666667 Combine like terms: -170.6666667 + 170.6666667 = 0.0000000 0.0000000 + -2.555555556x + x2 = 0 + 170.6666667 -2.555555556x + x2 = 0 + 170.6666667 Combine like terms: 0 + 170.6666667 = 170.6666667 -2.555555556x + x2 = 170.6666667 The x term is -2.555555556x. Take half its coefficient (-1.277777778). Square it (1.632716050) and add it to both sides. Add '1.632716050' to each side of the equation. -2.555555556x + 1.632716050 + x2 = 170.6666667 + 1.632716050 Reorder the terms: 1.632716050 + -2.555555556x + x2 = 170.6666667 + 1.632716050 Combine like terms: 170.6666667 + 1.632716050 = 172.29938275 1.632716050 + -2.555555556x + x2 = 172.29938275 Factor a perfect square on the left side: (x + -1.277777778)(x + -1.277777778) = 172.29938275 Calculate the square root of the right side: 13.126285947 Break this problem into two subproblems by setting (x + -1.277777778) equal to 13.126285947 and -13.126285947.Subproblem 1
x + -1.277777778 = 13.126285947 Simplifying x + -1.277777778 = 13.126285947 Reorder the terms: -1.277777778 + x = 13.126285947 Solving -1.277777778 + x = 13.126285947 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.277777778' to each side of the equation. -1.277777778 + 1.277777778 + x = 13.126285947 + 1.277777778 Combine like terms: -1.277777778 + 1.277777778 = 0.000000000 0.000000000 + x = 13.126285947 + 1.277777778 x = 13.126285947 + 1.277777778 Combine like terms: 13.126285947 + 1.277777778 = 14.404063725 x = 14.404063725 Simplifying x = 14.404063725Subproblem 2
x + -1.277777778 = -13.126285947 Simplifying x + -1.277777778 = -13.126285947 Reorder the terms: -1.277777778 + x = -13.126285947 Solving -1.277777778 + x = -13.126285947 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.277777778' to each side of the equation. -1.277777778 + 1.277777778 + x = -13.126285947 + 1.277777778 Combine like terms: -1.277777778 + 1.277777778 = 0.000000000 0.000000000 + x = -13.126285947 + 1.277777778 x = -13.126285947 + 1.277777778 Combine like terms: -13.126285947 + 1.277777778 = -11.848508169 x = -11.848508169 Simplifying x = -11.848508169Solution
The solution to the problem is based on the solutions from the subproblems. x = {14.404063725, -11.848508169}
| 9=w/35 | | 1.6/3.2=2.8/t | | k+-7=-3 | | -11=5y+12-4y-1 | | W/15=7/2 | | 6.6/1.2=w/4.2 | | -4+7x+-12x^2+21x^3=0 | | g+-5=-17 | | W/15=7/15 | | a+8=11-2a | | 8mn+9p=7k | | 4(-6x+7)=-212 | | 3(8x-1)-4x=17 | | 15/a=25/14 | | (x+2+3i)(x+2-3i)= | | 3d+4=2+3-.5 | | 10r^2-17r+6=0 | | -96-2x=129-11x | | 2(3a-1)=14 | | 8x+x-8+14=24 | | 87x^3-65x^3=12x^3 | | 24=y+10 | | K/20=13/50 | | x=x/25 | | -5n(-8)(1+7n)=-8 | | 3(8-3x)=123 | | Y=3-4ln(x^2-9) | | x^2+xy+y^2=1 | | -12=y/4 | | g(8b)=8x-1 | | 45x^2+30x^3=10x^4 | | 7.54=z/7 |